The History of the Horse: Interpreting the Classical Idea in Bartolomeo Rastrelli’s Equestrian Monument to Peter the Great - Chezhina, Julia I. (Actual Problems of Theory and History of Art, 2015)
The article describes the evolution of the idea underlying the first equestrian monument in Russia — the statue of Peter the Great on horseback by Bartolomeo Carlo Rastrelli. The author appeals to recent studies in the history of its creation and gives her own view of the well-known sculpture, focusing on the figure of the horse. A marble statue of a horse on a high pedestal found by Sergey Androsov in a private collection in France appeared to be a missing link in the history of Rastrelli’s monument. In Russia this sculpture made by an Italian master Pietro Baratta for a long time was thought to be lost. The statue represents the “Campidoglio horse of Marcus Aurelius from Rome”. It was specially commissioned by Peter I as a pattern for Rastrelli to work on the equestrian monument that was significant for the Emperor because of its conceptual meaning. The author of the article analyses the changes of the horses’ proportions and traits, and the details of horse trappings in every subsequent replica, paying much attention to some aspects that have never been mentioned before. Thus, she traces the consequent transformations in the interpretation of the equestrian statue’s image: from the Roman monument to the monumental sculpture of the Petrine era.